Man-machine interactions 2 - Czachórski, Tadeusz; Kozielski, Stanislaw; Stańczyk, Urszula (Berlin Springer, 2011)
Man-machine interaction is the interdisciplinary field, focused on a human and a machine in conjunction. It is the intersection of computer science, behavioural sciences, social psychology, ergonomics, security. It encompasses study, design, implementation, and evaluation of small- and large-scale, interacting, computing, hardware and software systems dedicated for human use. Man-machine interaction builds on supportive knowledge from both sides, the machine side providing techniques, methods and technologies relevant for computer graphics, visualisation, programming environments, the human side bringing elements of communication theory, linguistics, social sciences, models of behaviour. The discipline aims to improve ways in which machines and their users interact, making hardware and software systems better adapted to user's needs, more usable, more receptive, and optimised for desired properties. This monograph is the second edition in the series, providing the reader with a selection of high-quality papers dedicated to current progress, new developments and research trends in man-machine interactions area. In particular, the topical subdivisions of this volume include human-computer interfaces, robot control and navigation systems, bio-data analysis and mining, pattern recognition for medical applications, sound, text and image processing, design and decision support, rough and fuzzy systems, crisp and fuzzy clustering, prediction and regression, algorithms and optimisation, and data management systems.
Part I Invited papers -- Part II Man-machine interfaces -- Part III Robot control and navigation systems -- Part IV Bio-data analysis and mining -- Part V Pattern recognition for medical applications -- Part VI Sound, text and image processing -- Part VII Design and decision support -- Part VIII Rough and fuzzy systems -- Part IX Crisp and fuzzy clustering -- Part X Prediction and regression -- Part XI Algorithms and optimisation -- Part XII Data management systems
Electronic reproduction.
Keywords: User interfaces (Computer systems); Human-machine systems; Electronic books